The vulnerability aspect of happiness: The European middle class perspective - Péter Benczúr; Virmantas Kvedaras (European Commission, 2023)
This paper evaluates the importance of middle class vulnerability to poverty for subjective well-being (happiness) in European countries. Using the special module of the European Union Statistics on Income and Living Conditions micro-data on well-being and national aggregates from the World Happiness Report, the vulnerability indicator used is shown to be statistically significant for happiness perceptions at both the individual and aggregate levels. At the micro level, the economic importance of income vulnerability for the middle class is on a par with (or even greater than) economic factors such as severe material deprivation, difficulty of finding a job, or the acute financial burden of housing or debt repayments. We find that the lower income bound of the middle class (75% of the national median income) and not the poverty line (60% of the median) is more relevant for individual happiness of middle class members. The aggregate income vulnerability of the middle class is also one of the most significant factors affecting national happiness, along with gross domestic product per capita and perceptions of corruption. The results indicate that anxiety related to the (severe) downside risk of income has large costs in terms of happiness. They therefore support the development of policies to reduce income uncertainty.
Keywords: 330; happiness; income insecurity; middle class; poverty; subjective well-being; vulnerability